2021
DOI: 10.1037/pas0001013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Social Information Processing Application (SIP-AP) across genders, socioeconomic levels, and forms of aggression.

Abstract: The goals of the current study were to (a) replicate the factor structure of the Social Information Processing Application (SIP-AP), (b) evaluate the measurement invariance of the SIP-AP across genders, socioeconomic (SES) levels, and forms of aggression, and (c) assess the convergent validity of the SIP-AP through associations with aggression, social competence, and rule-breaking behavior. Participants were 189 racially/ ethnically diverse children (53% male; M age = 8.50 years) who completed the SIP-AP. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…They also found that children who generated a high proportion of reactive aggressive responses to hypothetical peer provocations were more likely to react aggressively when actually provoked in a later laboratory setting. Bookhout et al (2021) has recently replicated and extended these findings by showing that the number of aggressive responses a child generated to hypothetical peer provocations was positively correlated with the rate of aggressive rule-breaking behaviors observers recorded on the playground.…”
Section: Response Generationmentioning
confidence: 74%
“…They also found that children who generated a high proportion of reactive aggressive responses to hypothetical peer provocations were more likely to react aggressively when actually provoked in a later laboratory setting. Bookhout et al (2021) has recently replicated and extended these findings by showing that the number of aggressive responses a child generated to hypothetical peer provocations was positively correlated with the rate of aggressive rule-breaking behaviors observers recorded on the playground.…”
Section: Response Generationmentioning
confidence: 74%
“…Bookhout and colleagues (2021) validated the factor structure, measurement invariance, and convergent validity of the SIP-AP on the same sample used here. A five-factor model including the five constructs described above best fit the data.…”
Section: Methodsmentioning
confidence: 85%
“…Social information processing theory highlights the relevance of contextual influences on cognitions, such that violence exposure leads to the development of scripts that favor aggression (Huesmann, 1988). Indeed, studies have found that children exposed to economic disadvantage and community violence are more likely to support social goals favoring aggression or avoidance (Bookhout et al, 2021; Sypher et al, 2019). This suggests that different social contexts for diverse adolescents, including youth of color and those from different settings (e.g., urban and rural), may lead them to develop unique social goals.…”
mentioning
confidence: 99%